Effects of in vitro maturation media on in vitro fertility of porcine oocytes and early development of embryos - Viet Linh, Nguyen; Thi Hiep, Nguyen (Vietnam Journal of Biotechnology, 2020)
In pigs, embryo productivity is still lower than that in other livestocks. One of the reasons is incomplete maturation of porcine oocytes in in vitro conditions. Therefore in vitro maturation (IVM) plays a crucial role in in vitro production of porcine embryos. It provides prerequisite condition to in fertilization and subsequent development of porcine embryos. In a previous study, effects of NCSU-37-based medium and TCM-199-based media supplemented with porcine follicular fluid (pFF) or Fetal Bovine Serum (FBS) on in vitro maturation of Landrace oocytes collected in Vietnam have been compared, suggesting that NCSU-37 medium supplemented with 10% of porcine follicular fluid (pFF) had the highest rate of oocytes reach to metaphase II stage in comparison to those of the other two TCM-199-based media. In the present study, further experiments were carried out to evaluate the contribution of IVM media on fertilization capability and developmental competence. Porcine oocytes matured in vitro in 3 media: NCSU-37 supplemented with 10% pFF, TCM-199 supplemented with either 10% pFF or 10% FBS were subjected to in vitro fertilization and subsequent in vitro culture to monitor fertility and embryo development. The results showed that penetration and normal fertilization rates in both TCM-199 groups are both higher than that of NCSU-37 group. Moreover, the cleavage and blastocyst rates, and cell numbers of blastocysts which is a criterion for embryo quality were all higher in TCM-199 groups, especially in the group supplemented with pFF. It might be concluded that TCM-199 media supplemented with either pFF or FBS are suitable for effective in vitro maturation of Landrace porcine oocytes collected in Vietnam.